Whole genome analysis of the koa wilt pathogen (Fusarium oxysporum f. sp. koae) and development of molecular tools for early detection and monitoring - Dobbs, John, author; Stewart, Jane, advisor; Kim, Mee-Sook, committee member; Sloan, Daniel, committee member (Colorado State University. Libraries, 2019)
Pathogenic and non-pathogenic Fusarium oxysporum are morphologically indistinguishable from each other. Pathogenic F. oxysporum f. sp. koae (Fo koae) is a limiting factor for low to mid elevation, below 610m (2000 ft), Acacia koa forests and timber stands. These warmer, lower elevation sites are best suited for optimal growth of Acacia koa, but Fo koae hinders efforts to establish stands at these elevations. Detection of pathogenic isolates is necessary for informing land managers and disease resistance breeding programs. Current methods to distinguish pathogenic isolates are conducted through costly, extensive greenhouse virulence assays. Genomic comparisons of pathogens and non-pathogens such as amplified fragment length polymorphisms (AFLPs), single nucleotide polymorphisms (SNPs), Random Amplification of Polymorphic DNA (RAPDs), pathogenicity-related genes, and microsatellites have been effective for detecting pathogens, and these genomic comparisons are more time and cost effective than traditional greenhouse virulence assays. Chapter two of this thesis examined whole genomic comparisons of a pathogenic F. oxysporum f. sp. koae (Fo koae 44) and a F. oxysporum (Fo 170) isolate found to be non-pathogenic to Acacia koa, for the identification of genomic features that could be used to distinguish pathogenicity. Genome sizes were comparable at 48Mb and 50Mb, respectfully. Fo koae 44 and Fo 170 shared an average nucleotide identity of 96%. Eleven syntenic putative core chromosomes and one unique putative lineage-specific chromosome were identified when compared to a reference strain of F. oxysporum f. sp. lycopersici. Pathogenicity-related genes, including the secreted in xylem (SIX) genes, Fusarium transcription factors, and Fusarium transporters, and unique sequences were identified as exclusive to Fo koae 44 when compared to Fo 170. These variants were used to develop pathogen-specific primers. When tested on previously characterized pathogenic (highly and moderate virulence) Fo koae and low virulent or non-pathogenic Fo isolates, six primers only amplified moderate and highly virulent isolates of Fo koae. Haplotype networks were constructed based on sequencing data of previously characterized Fo koae and Fo isolates and field collected isolates with no pathogenicity data at the translation elongation factor 1-α and RNA polymerase II second largest subunit to determine the genetic relationships of these two groups. Some field collected isolates grouped with highly virulent Fo koae isolates. These results suggested that these field collected isolates might be highly virulent and contain the putative lineage-specific chromosome.